If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7st + 4t(t + s + 4) + -9 = 0 Reorder the terms: 7st + 4t(4 + s + t) + -9 = 0 7st + (4 * 4t + s * 4t + t * 4t) + -9 = 0 Reorder the terms: 7st + (4st + 16t + 4t2) + -9 = 0 7st + (4st + 16t + 4t2) + -9 = 0 Reorder the terms: -9 + 7st + 4st + 16t + 4t2 = 0 Combine like terms: 7st + 4st = 11st -9 + 11st + 16t + 4t2 = 0 Solving -9 + 11st + 16t + 4t2 = 0 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '9' to each side of the equation. -9 + 11st + 16t + 9 + 4t2 = 0 + 9 Reorder the terms: -9 + 9 + 11st + 16t + 4t2 = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 11st + 16t + 4t2 = 0 + 9 11st + 16t + 4t2 = 0 + 9 Combine like terms: 0 + 9 = 9 11st + 16t + 4t2 = 9 Add '-16t' to each side of the equation. 11st + 16t + -16t + 4t2 = 9 + -16t Combine like terms: 16t + -16t = 0 11st + 0 + 4t2 = 9 + -16t 11st + 4t2 = 9 + -16t Add '-4t2' to each side of the equation. 11st + 4t2 + -4t2 = 9 + -16t + -4t2 Combine like terms: 4t2 + -4t2 = 0 11st + 0 = 9 + -16t + -4t2 11st = 9 + -16t + -4t2 Divide each side by '11t'. s = 0.8181818182t-1 + -1.454545455 + -0.3636363636t Simplifying s = 0.8181818182t-1 + -1.454545455 + -0.3636363636t Reorder the terms: s = -1.454545455 + 0.8181818182t-1 + -0.3636363636t
| x+7-4=-15 | | 300=-(420*600*1500)-(-1c*600*1500)-(1000*600*1500) | | -14+3x=11 | | 3u-8=-20 | | -10y=x+21 | | 4y-5+y+19=5y+20-2y | | 10=5+5y | | 2x=x-46*x-86 | | .1x-33+.4x-40=180 | | 1x-3=9 | | -6=5u+4 | | n+20=100 | | -6=1/2x-4 | | 7(5+6x)=203 | | 10-4(6-x)+5= | | -6=1/2x4 | | 6000=3x/2(2x) | | 2x+25+65=180 | | 8(y-6)=7(y+2) | | -21.8-g=9.5 | | 2x+3x-x= | | 2w+2=16 | | -12+n=-36 | | 5+3n-4=9n+7-7n | | 6+5x=(x-3)-3(x-1) | | y=-x^2+500x | | 2x+2-3=5 | | f(x)=6x-17 | | -21.8+g=9.5 | | 5(2x+5y)= | | 4a+12=2a-8 | | 3z/5-3z/8=1 |